Natural resource management online in Caribbean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
the Online Proposal Appraisal (OPAL) programme has made available two management support programmes for use in the Caribbean context: 'Small Grants Program on Collaboration and Conflict in NRM' and the 'Small Grants Program on Collaborative Management of